2020
DOI: 10.1088/1361-6382/ab6d09
|View full text |Cite
|
Sign up to set email alerts
|

On the complexity of a 2  +  1-dimensional holographic superconductor

Abstract: We present the results of our computation of the subregion complexity and also compare it with the entanglement entropy of a 2 + 1-dimensional holographic superconductor which has a fully backreacted gravity dual with a stable ground sate. We follow the "complexity equals volume" or the CV conjecture. We find that there is only a single divergence for a strip entangling surface and the complexity grows linearly with the large strip width. During the normal phase the complexity increases with decreasing tempera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 64 publications
(164 reference statements)
3
23
0
Order By: Relevance
“…2, the values of HSC for the superconducting state is always larger than that for the normal state and increases as the temperature decreases. This result is in agreement with that reported in [39,43].…”
Section: The Results Of Operator O +supporting
confidence: 94%
See 3 more Smart Citations
“…2, the values of HSC for the superconducting state is always larger than that for the normal state and increases as the temperature decreases. This result is in agreement with that reported in [39,43].…”
Section: The Results Of Operator O +supporting
confidence: 94%
“…This phenomenon does not only appear in this system. In fact, the HSC of two different operators also exhibit different behaviors in 2+1 dimensional holographic superconductor, see [43], but the underlying mechanism remains mysterious.…”
Section: The Results Of Operator O −mentioning
confidence: 99%
See 2 more Smart Citations
“…The complexity essentially measures the difficulty of turning a quantum state into another and so it could reflect a phase transition on the boundary field theory. Holographic complexity has been studied in one dimensional s-wave superconductor in [36][37][38], p-wave superconductor in [39] and QCD phase transition [40]. It was found that holographic complexity behave in the different way with holographic entanglement entropy and both of them can reflect the one dimensional phase transitions.…”
Section: Introductionmentioning
confidence: 99%